Successful discontinuation of biological disease-modifying antirheumatic drugs in patients with rheumatoid arthritis in real-world settings. Issue 4 (4th July 2021) - Ochiai, Moeko; Tanaka, Eiichi; Sato, Eri; Inoue, Eisuke; Abe, Mai; Saka, Kumiko; Sugano, Eri; Sugitani, Naohiro; Higuchi, Yoko; Yamaguchi, Rei; Sugimoto, Naoki; Ikari, Katsunori; et al.
Abstract: Objectives: To analyze the proportion of successful biological disease-modifying antirheumatic drugs (bDMARDs) discontinuation and related factors in patients with rheumatoid arthritis (RA) in clinical settings. Methods: Among 1775 RA patients who started bDMARDs between 2003 and 2012, 43 patients with DAS28-ESR <3.2 at the time of bDMARD discontinuation were extracted. Patients were divided into two groups (bio-free success: BS and bio-free failure: BF groups) based on bDMARD usage and disease activity 1 year after discontinuation. We evaluated the proportion of bio-free success and assessed factors related to bio-free success. Results: Twenty-five patients (58.1%: BS group) maintained discontinuation of bDMARDs and DAS28-ESR <3.2 at 1 year after discontinuation. The median DAS28-ESR at bDMARD initiation was lower in the BS group than in the BF group (3.95 vs 5.04; p  = .04). The BS group experienced a larger decrease in average glucocorticoid (GC) dose during bDMARD use than the BF group (−3.0 mg/day vs 0 mg/day; p  = .01). Conclusion: bDMARDs were discontinued without flare up of RA in 58.1% of patients with RA in clinical settings. A lower DAS28-ESR at initiation and reduction of GC dose before discontinuation of bDMARD were important factors associated with bio-free success.